Tol2 transposon-mediated transgenesis in the Midas cichlid (Amphilophus citrinellus) — towards understanding gene function and regulatory evolution in an ecological model system for rapid phenotypic diversification. Issue 1 (December 2017) - Kratochwil, Claudius; Sefton, Maggie; Liang, Yipeng; Meyer, Axel
Abstract Background The Midas cichlid species complex (Amphilophus spp. ) is widely known among evolutionary biologists as a model system for sympatric speciation and adaptive phenotypic divergence within extremely short periods of time (a few hundred generations). The repeated parallel evolution of adaptive phenotypes in this radiation, combined with their near genetic identity, makes them an excellent model for studying phenotypic diversification. While many ecological and evolutionary studies have been performed on Midas cichlids, the molecular basis of specific phenotypes, particularly adaptations, and their underlying coding and cis-regulatory changes have not yet been studied thoroughly. Results For the first time in any New World cichlid, we useTol2 transposon-mediated transgenesis in the Midas cichlid (Amphilophus citrinellus ). By adapting existing microinjection protocols, we established an effective protocol for transgenesis in Midas cichlids. Embryos were injected with aTol2 plasmid construct that drives enhanced green fluorescent protein (eGFP ) expression under the control of theubiquitin promoter. The transgene was successfully integrated into the germline, driving strong ubiquitous expression of eGFP in the first transgenic Midas cichlid line. Additionally, we show transient expression of two further transgenic constructs, ubiquitin::tdTomato andmitfa::eGFP. Transgenesis in Midas cichlids will facilitate further investigation of the genetic basis of species-specific traits, many of which are adaptations. Conclusion Transgenesis is a versatile tool not only for studying regulatory elements such as promoters and enhancers, but also for testing gene function through overexpression of allelic gene variants. As such, it is an important first step in establishing the Midas cichlid as a powerful model for studying adaptive coding and non-coding changes in an ecological and evolutionary context.